Pendampingan Layanan Konseling Spiritual Teistik untuk Peningkatan Motivasi Menghafal Al-Qur’an di Madrasah Aliyah Negeri (MAN) 2 Bogor - Waki, Ahmad; Maulana, Ikhsan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The majority of people in Indonesia are Muslim, with the Koran and Sunnah as their guidelines. Nowadays, the activity of memorizing the Koran and memorizing the Koran in Indonesia is growing rapidly. This service is carried out to provide assistance and training in memorizing the Koran for students of Madrasah Aliyah Negeri (MAN) 2 Bogor, which in the past few years has experienced stagnation because there are no teachers who specialize in tahfiz and the support system is not working. Madrasah Aliyah Negeri (MAN) 2 Bogor does not offer one of its three majors related to tahfidz, but the author responded to the wishes of several students and their parents to provide assistance in the form of motivation to memorize the Al-Qur’an through theistic spiritual counseling methods. This service is carried out using mentoring and counseling methods for students taking part in the tahfiz program which has been stalled due to the absence of supervisors and allocation of costs related to the program. After the service, Madrasah Aliyah Negeri (MAN) 2 Bogor students who took part in the tahfiz program had very high interest and motivation to memorize the Koran. This shows that the tahfiz program needs to be developed.